Personality to Burnout: The Dual Roles of Psychological Empowerment and Transformational Leadership - Ouys Alkharani; Fendy Suhariadi; Mohammad Fakhrudin Mudzakkir; Rini Sugiarti; Elisabeth Supriharyanti (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Burnout is a condition that affects people in various occupations; however, there are limitations in the study of burnout in the service sector. Objective: This study aims to determine the influence of Big Five personality on burnout mediated by Psychological Empowerment and moderated by transformational leadership. Methods: This research combines explanatory research methods with quantitative methodology. The population of this study were all employees of PT Telkom Access Divre IV, totalling 243 people in the service operations section. The measurement methods used in this study are the Big Five Inventory (BFI) scale, the 12-item Burnout Assessment Tool (BAT), the 12-item Psychological Empowerment Scale, and the Bass Multifactor Leadership Questionnaire. SmartPLS 3.2.9 was used to conduct data analysis. Results: The results showed that the Big Five personality affects burnout, and psychological empowerment affects burnout and can mediate the effect of the Big Five personality on burnout. Transformational leadership can moderate the impact of Big Five personality on burnout. As with all empirical research, the shortcomings of this study must be addressed. First, the model has limited job demands and resources variables as the study focuses on individual variations rather than job features. Second, since this study used self-reported surveys, common method variance may be the cause of the relationship. Conclusion: These findings highlight that burnout is not solely driven by personality, but by how personal traits interact with empowerment processes and supportive leadership, offering important implications for theory development and practical interventions in high-demand service environments.